Village Government Policy in Reducing Poverty - Pramono, Wahyu; Mulia, Rizki Afri (Jurnal Ilmiah Ekotrans & Erudisi, 2023)
This research aims to find out how local government policies reduce poverty in Baringin Village, Lubuk Kilangan District, West Sumatra. Includes policy strategies, policy steps, and follow-up Local government policies and village community development, as well as factors that influence local government policies not being optimal in reducing poverty in Baringin District, include budget factors, community factors, resource factors, community factors, and apparatus attitudes. The research method used is qualitative-descriptive. In collecting data, field research was carried out using observation techniques with the aim of directly knowing the data needed. Then carry out interview techniques and conduct library research by searching for documents related to local government policy issues related to reducing poverty in Baringin Village. The results of this research show that the local government's policy in reducing poverty in Baringin Subdistrict is quite good. This can be seen from the policy programs implemented by the subdistrict government, which can be directly felt by the community. However, in the implementation of local government policies to reduce poverty, there are of course obstacles or factors such as budget, lack of communication, less creative human resources, and less professional attitudes of officials.